An Assessment on the Students’ Level of Earthquake Awareness and Preparedness on “The Big One” - De Guzman, Aaron Joseph B.; Godoy, Aldrine M.; Nicodemus, Mary Mae C.; Ramos, Lermishane Love F.; Basilio, Eleonor R. (Three E Science Institute, 2023)
Since the Philippines has been subjected to numerous seismic events throughout the past several decades, it is only prudent to be aware and prepared for what will unavoidably happen when the Marikina West Valley Fault System moves. The study aims to assess the College of Science students' earthquake awareness and preparedness level, an essential part of their understanding of proper response and management in natural disasters. It will also allow the community and the environment to establish necessary precautions. A descriptive-survey study approach was applied to assess the level of awareness and preparedness of 160 respondents from all year levels from the College of Science at Bulacan State University. Results show that most respondents are highly aware and prepared for an earthquake. However, low levels were shown in some components of earthquake public awareness and disaster risk reduction preparedness. This includes the respondents' contingency plan awareness, security of household materials, and coordination with local government units regarding potentially high-risk objects. A significant difference was also seen in the respondents' awareness of the existing contingency plan and participation in first-aid training for risk reduction. In addition, first-year students mainly acquired their awareness from School/Office, while second- to fourth-year students acquired it mainly from the Internet. With the obtained results, the authors created a proposed intervention consisting of programs regarding the university's Incident Command System, Contingency Plan, and Disaster Risk Reduction Management.